Pengakuan Hukum Adat Aceh Yang Berbasis Islam di Indonesia - Laras Medina Pranitia; Tyur Reggina Dewanti; Nina Fitria Sukma; Dwi Desi Yayi Tarina (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Indonesia consists of many ethnic groups and each tribe has its own customs in its territory. However, these differences in customs do not undermine national unity, because the Indonesian people are aware of the Indonesian nation's motto, Bhinneka Tunggal Ika. Since ancient times there have been customs that have lived in society. In the process of customary development, rules emerge that develop in society which are called customary law. Aceh is a region that has special autonomy in the affairs of its regional government because it is one of the provinces in Indonesia which is strongly supported by customary social law. Unlike other provinces in Indonesia, Aceh was legislated under a national law that has an Islamic religious background. The customary law that applies in Aceh is closely related to sharia principles and plays an important role in social life.